THE AFTERLIFE OF VOËLVRY IN POST-APARTHEID SOUTH AFRICA - Truscott, Ross (PINS-Psychology in Society, 2025)
Kombuis, Koos (2009) Short drive to freedom: A personal perspective on the Afrikaans rock rebellion. Cape Town: Human & Rousseau. ISBN 978 0 7981 5098 0. Pages 256. In his recent memoir, playfully titled Short drive to freedom, Afrikaans-speaking musician and author, Koos Kombuis, contributes to the history of the “Afrikaner Alternative Movement” by offering “a personal perspective on the Afrikaans rock rebellion.” Although Kombuis recounts events prior to and following the development of Voëlvry, which reached its highpoint in a 1989 nationwide tour, it is Voëlvry to which his narrative constantly returns. It was during this tour that Kombuis, together with manager, Dagga-Dirk Uys and musicians, Bernoldus Niemand (James Phillips), Johannes Kerkorrel (Ralph Rabie), Piet Pers (Gary Herselman), Hannepoort van Tonder (Jannie van Tonder), Karla Krimpalien (Tonia Selley) and Willem Moller played to packed audiences of mostly young white Afrikaners at university campuses and town halls, preaching against the insanity of apartheid. With sponsorship from the Vrye Weekblad, the then newly launched anti-establishment weekly newspaper, and from Shifty Records, an independent South African recording company, and armed with music, irony, alcohol, dagga (marijuana) and intense frustration at the suffocation of life under apartheid, the musicians became a scathing satire of the ideals, institutions, idiosyncrasies and monuments of Afrikaner Nationalism.